On the design of a neutral business tax under uncertainty - Devereux, M; Bond, S (1995)
This paper extends the results of Boadway and Bruce (Journal of Public Economics, 1984, 24, 231–239) and Fane (Journal of Public Economics, 1987, 33, 95–105) to describe a tax on business profits which is neutral with respect to investment and wind-up decisions, and default outcomes, under uncertainty and bankruptcy risk. The tax base allows deductions for depreciation and the cost of finance, but requires knowledge of neither true economic depreciation nor the firm's required rate of return. We show that the tax must treat taxable profits and losses symmetrically, and that the tax rate must be a known constant, even in the special case when the tax base coincides with the economic rent earned in each period.